Contributions of Neuroscience Knowledge to Teachers and Their Practice. (October 2019) - Dubinsky, Janet M.; Guzey, S. Selcen; Schwartz, Marc S.; Roehrig, Gillian; MacNabb, Carrie; Schmied, Astrid; Hinesley, Vicki; Hoelscher, Mary; Michlin, Michael; Schmitt, Lee; Ellingson, Charlene; Chang, Zhengsi; et al.
While neuroscience has elucidated the mechanisms underpinning learning and memory, accurate dissemination of this knowledge to teachers and educators has been limited. This review focuses on teacher professional development in neuroscience that harnessed the power of active-learning strategies and best educational practices resulting in increased teacher and student understanding of cognition and brain function. For teachers, the experience of learning a novel subject in an active manner enabled them to subsequently teach using similar strategies. Most important, participants viewed neuroscience as a frame for understanding why active-learning pedagogies work to engage and motivate students. Teachers themselves made connections applying neuroscience concepts to understand why learner-centered pedagogies are effective in promoting higher order thinking and deep learning in their students. Teachers planned and embraced pedagogies involving modeling, experimentation, discussion, analysis, and synthesis, increasing classroom cognitive engagement. Comprehending that everyone is in charge of changing their own brains is a tremendously powerful idea that may motivate science and non-science teachers to provide students opportunities to actively engage with content. Neuroscience courses for preservice and in-service teachers, provided as collaborations between scientists and teacher educators, can result in improved science education, pedagogy, and understanding of neuroscience.